Abstract ID: 97 A Monte Carlo study of resolving the radiation dose through the detection of Cerenkov radiation in Boron Neutron Capture. (October 2017) - Shu, Diyun; Tang, Xiaobin; Geng, Changran; Gong, Chunhui; Shao, Wencheng; Ai, Yao; Zhang, Xudong
Abstract : Radiation dose in boron neutron capture therapy (BNCT) is determined by both the epithermal neutron beam and Boron-10 distribution[1, 2] . It is thus more complex and important to monitor the radiation dose comparing to other radiation treatment modalities. In this study, we investigated the feasibility of resolving the radiation dose with respect to the change of beam property and Boron-10 concentration through the detection of Cerenkov radiation during BNCT. Monte Carlo toolkit Geant4 was used to simulate the irradiation of epithermal neutron beam on phantom containing tumor region[3] . Cerenkov can be generated during BNCT and it is expected to be correlated with gamma dose. The depth and radial distributions of gamma dose were obtained under different characteristics of boron concentration and epithermal neutron beam. The relationship between the number of Cerenkov photons and gamma dose was explored based on simple phantom and Chinese reference radiation phantom. Results showed that the gamma dose is almost unchanged under different boron concentration distributions, even if the relative change of boron concentration reached 60 percent. The changes in the characteristics of epithermal neutron beam directly leads to the changes in the gamma dose. This indicated that gamma dose can be used to reflect the stability and delivery accuracy of epithermal neutron beam. Meanwhile, the response relationship between the number of Cerenkov photons and gamma dose was observed. As a preliminary result, it suggests the potential feasibility to monitoring the gamma dose and the stability of the epithermal neutron beam through the detection of Cerenkov radiation emitted during BNCT.